Influence of coping strategies and perceived social support on depression among elderly people in Kajola local government area of Oyo State, Nigeria (2017)
Health related issues like Dysphoric mood or loss of interest or pleasure in life and in free time activities, poor appetite, insomnia, psychomotor agitation or retardation, feelings of excessive guilt, lack of concentration, inability to think, withdrawn, despondent, disturbed sleep and reduced appetite observed among elderly people attracted the attention of this study to examine the influence of coping strategies and perceived social support on depression among elderly people. This study adopted cross sectional research design to examine the influence of coping strategies and perceived social support on depression among elderly people who are 60 years and above in kajola local government area of Oyo state, Nigeria. Purposive sampling technique was used systematically to select 200 elderly people that participated in the study. The result of the finding revealed that elderly people with low perceived social support reported higher depression than their counterpart with high perceived social support at [t(198)=-12.41, p<.05] and it was also discovered that elderly people with low coping strategies reported higher depression than their counterpart with high coping strategies among elderly people at [t(198)=-12.41, p<.05]. More so, the result of the findings depicted that, there was significant joint influence of coping strategies and perceived social support on depression [F(2,197)=43.86; p<0.05; R2=0.29] and further analysis revealed that coping strategies and perceived social support made significant independent contribution to depression among elderly people in kajola local government area of Oyo state, Nigeria [β=-0.15; t = -2.40; p<0.05 & β=1.24; t = 9.31; p<0.05]. This study concluded with discussion of findings and recommend that family, relative, neighbour and government should provide adequate support to the elderly people in order to reduce depressive symptoms and mortality rate among them